DESARROLLO DE UN SOFTWARE PARA LA GESTIÓN DE CITAS DEL CONSULTORIO VETERINARIO CORAZÓN DE JESÚS A.L.R 2020 - Padilla Espino, Miguel Fernando (2022)
The research carried out which bears the title of development of a software for the management of the veterinary office "Corazón de Jesús A.L.R.", 2020 seeks to provide a computer solution that allows optimizing the processes of the veterinary office in an appropriate way. For the proposed purpose, it was determined that through the application of a traditional software development model in conjunction with the RUP methodology, the construction of the software will be carried out in an organized manner as a result of the research. The programming languages to be used were C # and Javascript, and Microsoft SQL Server was the database manager. KEYWORDS: Software, Rational Unified Process, SQL Server, C#, methodology